Makna Agama dan Budaya bagi Orang Jawa - Muhammad Idrus (Universitas Islam Indonesia, 2007)
Seeking the truth, for Javanese people, is not solely based on rational consideration. In many cases, this is also correlated with spiritual one, and even, to some extent, the previ- ous is undermined by the latter. This situation poses Javanese people on a cross-road between religion and culture, and for them it is the best way to practice both. Keywords: Japanese, religion, culture, practice.on, culture, practice.